TECHNOLOGY ACCEPTANCE EVALUATION OF POSYANDU APPLICATION AMONG COMMUNITY HEALTH WORKERS: THE INTENTION OF USE AND PARTICIPATION IN VALUE CO-CREATION - Lathifah, Azmii
Digitalization in health services cannot be avoided. This process needs support from all sectors, especially the community in society. Therefore, community empowerment is essential. Posyandu is an implementation of community empowerment for maternal and child health services, which is carried out from, by, for the community and is guided by related officers. Community representatives in implementing this activity can be called cadre or community health workers (CHW). iPosyandu as a mobile Health application (mHealth app), was introduced to assist community health workers in reporting and monitoring Posyandu data online. Unfortunately, they still provide data on paper, which takes a long time to store. As a result, policymaking and implementation are delayed, especially in maternal and childcare, particularly in reducing maternal mortality and stunting, which have not reached the target of the World Health Organization (WHO). This study aims aim to identify and explore the reason of the factor that influences Posyandu application intention behaviour usage by expanding the Unified Theory of Acceptance and Use of Technology (UTAUT) and intention to participate in value co-creation among community health workers.